2015
DOI: 10.1002/clen.201300886
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Assessment of Heavy Metal Contamination in Surface Sediments from the Inflow Rivers of Taihu Basin

Abstract: The spatial variation, potential sources, and ecological risk of heavy metals (Cd, Co, Cr, Cu, Mn, Hg, Ni, Pb, and Zn) in surface sediments from the typical inflow rivers in Taihu Basin were investigated in June 2010. The results showed that the heavy metal concentrations varied greatly and spatially, and higher metal contamination mainly occurred in the northern and northwestern regions in Taihu Basin. Multivariate statistical analysis demonstrated that Mn might originate from natural sources, whereas Cd, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Mathematically, EF is expressed as:EF = (M/X) sample /(M/X) background where M is the evaluated element, X is the reference element, and (M/X) sample and (M/X) background are the ratios of an evaluated element and the reference element in the examined and geochemical background, respectively. As a geochemical common factor, aluminum has often been used as the reference element [13]. Thus, the EFs were calculated using Al as reference element and heavy metal background values of soils in Jiangsu Province [14] were chosen as the background.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mathematically, EF is expressed as:EF = (M/X) sample /(M/X) background where M is the evaluated element, X is the reference element, and (M/X) sample and (M/X) background are the ratios of an evaluated element and the reference element in the examined and geochemical background, respectively. As a geochemical common factor, aluminum has often been used as the reference element [13]. Thus, the EFs were calculated using Al as reference element and heavy metal background values of soils in Jiangsu Province [14] were chosen as the background.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the EFs were calculated using Al as reference element and heavy metal background values of soils in Jiangsu Province [14] were chosen as the background. An EF < 2 represents no contamination to minor contamination, 2–5 represents moderate contamination, 5–20 represents significant contamination, 20–40 represents very high contamination, and >40 represents extremely high contamination [10,13].…”
Section: Methodsmentioning
confidence: 99%
“…The most widely used forms of empirical SQGs are based on sediment chemistry and biological effects, and on mechanistic techniques related to equilibrium partitioning 47 . To assess sediment pollution, researchers have developed several SQGs using large data sets 48 . One of the most important methods developed in this area belongs to Long and MacDonald 49 and MacDonald et al 50 , who suggest "consensus-based" SQGs for assessing the environmental effects of metals.…”
Section: Sediment Quality Guidelines (Sqgs)mentioning
confidence: 99%
“…Heavy metals are important constituents of the environment and their inputs always result in the deterioration of the aquatic environment [16]. Most studies have reported that Cu, Cr, Co, and Ni can originate primarily from industrial and urban activities such as electrical machinery operation, chemical production, automobile exhaust, and mining [1,12,[15][16][17].…”
Section: Physicochemical Properties and Heavy Metals In Watermentioning
confidence: 99%